A Study on Health Issues of Scalp Hair Among Final Professional undergraduates in the Faculty of Indigenous Medicine - Buddhadasa, H.M.K.A.; Munasinghe, D.A.L. (International Journal of Research Publication and Reviews, 2026)
Hair is an important aesthetic and psychological factor that contributes significantly to an individual’s personality. In both males and females, hair plays a vital role in social perception and self-esteem. The condition of the scalp and hair can have considerable psychological impacts, where even minor changes such as early hair loss or greying may affect a person's quality of life. This study, conducted from September 2023 to January 2024, aimed to assess common scalp and hair health issues among final professional undergraduates (2017/18 batch) of the Faculty of Indigenous Medicine. A total of 103 students were selected using a random sampling method. Data were collected through a structured Google Form questionnaire and analyzed using Microsoft Excel, with results presented in graphs. The most frequently reported scalp and hair issues included hair fall, dandruff, split ends, damaged hair, dry scalp, and oily scalp. Among these, hair fall was the most prevalent, affecting 85% (n=87) of students, followed by dandruff (55%, n=57). Oily scalp was the least reported condition. Several students reported experiencing multiple hair issues simultaneously. Female students exhibited a higher prevalence of hair and scalp problems compared to males. Contributing factors identified included place of residence, sleep patterns, family history, frequency and timing of hair washing, type of water and cleansing agents used, and hair styling practices. The study found that family history had minimal influence, while hostel living conditions and inadequate sleep were associated with increased hair issues. Based on these findings, it is suggested that morning hair washing with warm water and appropriate cleansing agents may help in managing scalp hair issues effectively.
Keywords: Scalp hair issues; hair fall; dandruff; medical undergraduates; Indigenous Medicine; Khalitya; poor sleep; questionnaire survey